PENGARUH DEBT TO EQUITY RATIO (DER) DAN DEBT TO ASSET RATIO (DAR) TERHADAP KINERJA PERUSAHAAN DI SEKTOR KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Azzalia Feronicha Wianta Efendi; Seto Sulaksono Adi Wibowo (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2017)
Comparison between self-capital and foreign capital structured in capital structure into an instrument used by companies to plan and take debt usage policies in maximizing profits and stock prices company. Banking in conducting its operational activities must have a large enough capital and well structured, in order to avoid the financial problems. To attract investors, banks are urged to improve their performance that can be assessed from bank financial statements in providing information to investors. This study aims to determine the partial influence of capital structure proxyed with leverage ratios those are Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR) to company performance seen from its profitability with Return on Asset (ROA) and Return on Equity (ROE) of banking companies for 3 years. This study used a sample of 30 banks for 3 years from 2013-2015 by using panel data regression analysis. The results showed partially DER variables affect the ROA and ROE, and partially DAR variables affect the ROA and no effect on ROE. This study is limited to a banking company only and within 3 years, it should be able to use other corporate sectors and longer periods of time. Further research is expected to add research variables, corporate sectors, samples and add to the study period. Keywords: Capital Structure, Banking, Corporate Performance, Leverage, Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR), Return on Assets (ROA), Return on Equity (ROE)